2021
DOI: 10.4103/aam.aam_12_20
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Content of Rice Meals Sold in a Nigerian Market Population with a High Prevalence of Hypertension

Abstract: Context: Some market populations in Nigeria have been shown to have high prevalence of hypertension. Current evidence includes environmental pollutants such as heavy metals as risk factors for hypertension. Aim: To study the heavy metal content of rice meals sold in a market population with a high prevalence of hypertension. Settings and Design: This was a descriptive, cross-sectional study conducted in Ogbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These activities affect food safety, an essential component of food security, and as a result pose serious threat to human health (Munir et al, 2022;Ahmed et al, 2021;Bakshi and Banik, 2018). Presence of various toxic metals in foods harvested and consumed in Nigeria have been reported (Anakwue et al, 2021;Omeje et al, 2021;Sadi et al, 2021;Ayanda et al, 2020;Maduforo et al, 2020). Study observed that chromium (Cr) and lead (Pb) found in cereals and cereal-based food products consumed in Nigeria were higher than Food and Agricultural Organization/ World Health Organization (FAO/WHO) safe limits (Arigbede et al, 2019).…”
Section: Effects Of Heavy Metals Pollution On Food Safety and Securitymentioning
confidence: 99%
“…These activities affect food safety, an essential component of food security, and as a result pose serious threat to human health (Munir et al, 2022;Ahmed et al, 2021;Bakshi and Banik, 2018). Presence of various toxic metals in foods harvested and consumed in Nigeria have been reported (Anakwue et al, 2021;Omeje et al, 2021;Sadi et al, 2021;Ayanda et al, 2020;Maduforo et al, 2020). Study observed that chromium (Cr) and lead (Pb) found in cereals and cereal-based food products consumed in Nigeria were higher than Food and Agricultural Organization/ World Health Organization (FAO/WHO) safe limits (Arigbede et al, 2019).…”
Section: Effects Of Heavy Metals Pollution On Food Safety and Securitymentioning
confidence: 99%